Influence of cytokine and cytokine receptor gene polymorphisms on the degree of liver damage in patients with chronic hepatitis C - Moreira, Sara Tatiana; Silva, Giovanni Faria [UNESP]; de Moraes, Camila Fernanda Verdichio [UNESP]; Grotto, Rejane Maria Tomasini [UNESP]; de Moura Campos Pardini, Maria Inês [UNESP]; Bicalho, Maria da Graça; Moliterno, Ricardo Alberto (Elsevier, 2016)
Hepatic fibrosis may be the result of repetitive injury to hepatocytes caused by HCV infection and the immune response to it. Cytokines regulate the inflammatory response to injury and modulate hepatic fibrogenesis. Single nucleotide polymorphisms (SNPs) located in cytokine genes may influence the cytokine expression and secretion that may contribute to hepatic fibrogenesis in HCV infection. The aim of this study was to determine the genotype of 22 SNPs found in the genes of 13 cytokines/cytokine receptors to assess the influence of polymorphic variants on the stage of liver damage in Brazilian patients chronically infected with HCV genotype 1 only. 141 unrelated patients were grouped according to their stage of fibrosis: absence of fibrosis or patients in the initial stages of fibrosis (F0-F2, n = 84), patients with advanced stages of fibrosis or cirrhosis (F3-F4, n = 57), without cirrhosis (F0-F3, n = 103), and with cirrhosis (F4, n = 38). The comparison of frequencies in each sub-sample was performed by 2 × 2 contingency tables using the chi-square or Fisher's exact test. Stepwise logistic regression was also used to assess independent associations between cirrhosis or fibrosis with polymorphic variants. The TNFA-308G:A genotype conferred increased risk of fibrosis and cirrhosis. The TNFA-238G:G genotype was associated with protection from cirrhosis. The IL10-819C:T genotype conferred protection from fibrosis and the IL1B-511C:T genotype conferred increased risk of cirrhosis. Some of these genotypes showed results on the borderline of statistical significance in the bivariate analysis. We conclude that gene variants of cytokines/receptors may influence liver damage in patients chronically infected by HCV genotype 1.
Keywords: Cytokine; Hepatic cirrhosis; Hepatitis C; Liver fibrosis; Polymorphism